AVALIAÇÃO DAS ATIVIDADES GENOTÓXICA E ANTIGENOTÓXICA DE DUGUETIA FURFURACEA EM BACTÉRIAS E CAMUNDONGOS - SILVA, Carolina Ribeiro e (2008)
The plant Duguetia furfuracea (St. Hil.) Benth and Hook. f. (1862), belongs to the family Annonaceae, is popularly known as sofre‐do‐rim‐quem‐quer, araticum‐do‐cerrado and ata‐do‐mato. This plant occurres in several Brazilian states, as Amazonas, Bahia, Distrito Federal, Goiás, Minas Gerais, Mato Grosso, Mato Grosso do Sul and São Paulo. It is commonly used by people as anti‐rheumatic and to cure renal colic. Previous studies have described therapeutic activity of this plant with trypanocidal, antiplasmodial and antiprotozoal effects. Due to the large utilization of this plant by the local people, the present work aimed to evaluate the genotoxic/mutagenic, antigenotoxic/antimutagenic and cytotoxic activities of lyophilized leaf extract of D. furfuracea by the lisogenic induction test (Inductest) and the mice bone marrow micronucleus assay (Micronucleus Test). The lisogenic induction test was performed according Moreau et al., (1976) using E. coli WP2s(λ) and RJF013 strains. To evaluate the genotoxic and toxic activities, the doses employed were 1 mg, 2 mg, 5 mg e 10 mg, while to evaluate the antigenotoxic action the doses were of 0,5 mg, 1 mg, 2 mg, 5 mg e 10 mg co‐treated with 0,5 μg de mitomycin C. Micronucleus test in the bone marrow of mice was performed according to Schmid (1975). To evaluate mutagenic activity, mice were treated with three different doses of plant extract (100, 200 and 300 mg/Kg body weight), to evaluate antimutagenic activity, mice were treated with the same doses co‐administered with 4 mg/kg of mitomycin C. The genotoxic action was evaluated by the frequency of micronucleated polychromatic erythrocytes (MNPCE) and cytotoxicity was evaluated by the polychromatic and normochromatic erythrocytes ratio (PCE/NCE). The results obtained from the evaluation of mutagenicity of this plant showed that the extract of D. Furfuracea didn t increase significantly (p>0.05) the frequency of MNPCE compared to negative control. Cytotoxicity was evident in all applied doses (p<0.05). Concerning antimutagenicity, all doses of extract reduced significantly the frequency of MNPCE compared to the positive control group (p<0.05). In both tests, the results obtained demonstrated that the extract of D. furfuracea presented cytotoxicity; however, it didn t show genotoxic or mutagenic effects in bacteria and mice bone marrow respectively. In the other hand, it was observed a antigenotoxic and antimutagenic action.